Internalisasi Nilai Ekonomi Islam sebagai Ekosistem Ekonomi di Era Metaverse - Nafiah Nafiah (Institut Agama Islam Negeri Ponorogo, 2022)
The emergence of metaverse technology is a challenge for the digital economic order in Indonesia, especially in the internalization of Islamic economic values. The depravity of the capitalist economy that cannot answer the challenges of a economic principle is the answer to its failure to respond to the community's economic ecosystem in the metaverse era. This article aims to analyze and examine the internalization of Islamic economic values as a just economic ecosystem in Indonesia. This research is qualitative with literature review and online observation with an ethnographic approach. The study results show that Islamic economic values can be a solution to problems in the metaverse, especially in the distribution of welfare. The Indonesian economy, which is based on the MSME sector (micro, small and medium enterprises), has long been recognized as a significant business sector in the fundamental role of the economy. The concept of waqf in Islam has proven to be a means of sharing welfare compared to other systems. In the end, the Islamic economic system can achieve a welfare state that encourages the achievement of human capital building and improvements in social sectors compared to the capitalist economic system. In the metaverse, the principles of Islamic economics encourage macroeconomic progress and embrace microeconomic practitioners while still having the rights regulated in Islamic economics; even technicians who are not directly involved in the metaverse also have rights regulated in Sharia and Fiqh. Economic values do regulate not only principles but also policy products. This makes Islamic economics included in all lifelines, including in the metaverse where everything is interconnected, so everyone will know that Islamic economics does not harm anyone and allows prosperity for the community.